MANAJEMEN MUSYAWARAH GURU MATA PELAJARAN (MGMP) DALAM MENINGKATKAN PROFESIONALISME GURU AKIDAH AKHLAK MTs NEGERI DI KABUPATEN KUDUS TAHUN PELAJARAN 2015/2016 - Sutikat, Sutikat (Pascasarjana IAIN Kudus, 2017)
This study is aimed at investigating directly management of MGMP Akidah Akhlak in Madrasah Tsanawiyah Negeri in Kudus Regency. The formulated problems in this study are: 1) How is management of MGMP Akidah Akhlak in MTs Negeri in Kudus Regency in the academic year 2015/2016? 2) How are the efforts to improve Akidah Akhlak teachers’ professionalism in MTs Negeri in Kudus Regency in the academic year 2015/2016? 3) What are the roles of Akidah Akhlak teachers in fostering students’ morals in MTs Negeri in Kudus Regency in the academic year 2015/2016? This study used the qualitative method, namely a research method employed to research the objects’ conditions naturally, in which the researcher acted as a key instrument. Data collection employed the methods of interview, observation, documentation, and triangulation. The method of data analysis used a method developed by Miles and Huberman with three steps, namely data reduction, data presentation, drawing a conclusion, and verification. The stages in this study comprised: 1) the preparation stage, 2) the implementation stage, and 3) the report-making stage. Moreover, the study locations were in Madrasah Tsanawiyah Negeri in Kudus Regency. The results of this study indicated that, 1). Management of MGMP Akidah Akhlak held in MTs Negeri in Kudus Regency can be explained as follows: a) MGMP Akidah Akhlak in MTs Negeri in Kudus is an association platform for Akidah Akhlak teachers in Kudus Regency which functions as a medium to communicate each other, learn and exchange ideas and experience to improve teachers’ performance as practitioners of learning-change in classrooms, b) with regard to program implementation of MGMP Akidah Akhlak in MTs Negeri in Kudus Regency, the expected results are that Akidah Akhlak teachers have the same perceptions and high commitments to improve their career collected in the activities of MGMP Akidah Akhlak, and are able to enhance motivation, frequency and intensity of career development activities. 2). The strategies in improving teachers’ professionalism and competence conducted by MGMP Akidah Akhlak in MTs Negeri in Kudus Regency are: a) through various strategies in the form of education and training, for instances, In house training (IHT) and school partnership, group discussion, seminar, workshop on writing teaching materials/books and developing learning media, b) conducting learning and teaching activities which involve lecturers, teaching colleagues, guide teachers, and principals. 3). Responsibility of Akidah Akhlak teachers is very close with instilling religious values in students. Therefore, Akidah Akhlak teachers must be competent and professional in the learning and teaching process.